Rituximab maintenance versus observation alone in patients with chronic lymphocytic leukaemia who respond to first-line or second-line rituximab-containing chemoimmunotherapy: final results of the AGMT CLL-8a Mabtenance randomised trial - Greil, Richard; Obrtlíková, Petra; Smolej, Lukáš; Kozák, Tomáš; Steurer, Michael; Andel, Johannes; Burgstaller, Sonja; Mikušková, Eva; Gercheva, Liana; Nösslinger, Thomas; Papajík, Tomáš; Ladická, Miriam; et al. (The Lancet. Haematology, 2016)
BACKGROUND: In many patients with chronic lymphocytic leukaemia requiring treatment, induction therapy with rituximab plus chemotherapy improves outcomes compared with chemotherapy alone. In this study we aimed to investigate the potential of rituximab maintenance therapy to prolong disease control in patients who respond to rituximab-containing induction regimens. METHODS: In this randomised, international, multicentre, open-label, phase 3 clinical trial, we enrolled patients who had achieved a complete response (CR), CR with incomplete bone marrow recovery (CRi), or partial response (PR) to first-line or second-line rituximab-containing chemoimmunotherapy and randomly assigned them in a 1:1 ratio (central block randomisation in the electronic case report form system) to either intravenous rituximab 375 mg/m(2) every 3 months, or observation alone, for 2 years. Stratification was by country, line of treatment, type of chemotherapy added to the rituximab backbone, and degree of remission following induction. The primary endpoint was progression-free survival. Efficacy analysis was done in the intention-to-treat population. This is the final, event-triggered analysis. Final analysis was triggered by the occurrence of 92 events. This trial is registered with ClinicalTrials.gov, number NCT01118234. FINDINGS: Between April 1, 2010, and Dec 23, 2013, 134 patients were randomised to rituximab and 129 to observation alone. Median observation times were 33·4 months (IQR 25·7-42·8) for the rituximab group and 34·0 months (25·4-41·9) for the observation group. Progression-free survival was significantly longer in the rituximab maintenance group (47·0 months, IQR 28·5-incalculable) than with observation alone (35·5 months, 95% CI 25·7-46·3; hazard ratio [HR] 0·50, 95% CI 0·33-0·75, p=0·00077). The incidence of grade 3-4 haematological toxicities other than neutropenia was similar in the two treatment groups. Grade 3-4 neutropenia occurred in 28 (21%) patients in the rituximab group and 14 (11%) patients in the observation group. Apart from neutropenia, the most common grade 3-4 adverse events were upper (five vs one [1%] patient in the observation group) and lower (three [2%] vs one [1%]) respiratory tract infection, pneumonia (nine [7%] vs two [2%]), thrombopenia (four [3%] vs four [3%]), neoplasms (five [4%] vs four [3%]), and eye disorders (four [3%] vs two [2%]). The overall incidence of infections of all grades was higher among rituximab recipients (88 [66%] vs 65 [50%]). INTERPRETATION: Rituximab maintenance therapy prolongs progression-free survival in patients achieving at least a PR to induction with rituximab plus chemotherapy, and the treatment is well tolerated overall. Although it is associated with an increase in infections, there is no excess in infection mortality, suggesting that remission maintenance with rituximab is an effective and safe option in the management of chronic lymphocytic leukaemia in early treatment phases. FUNDING: Arbeitsgemeinschaft Medikamentöse Tumortherapie gemeinnützige GmbH (AGMT), Roche.
Keywords: Bendamustine Hydrochloride; Rituximab; Male; vidarabin; Survival Rate; Antineoplastic Combined Chemotherapy Protocols; Cyclophosphamide; Neoplasm Staging; Vidarabine; Adult; Aged; dospělí; mužské pohlaví; senioři; rituximab; Immunotherapy; Leukemia, Lymphocytic, Chronic, B-Cell; senioři nad 80 let; lidé; ženské pohlaví; Humans; protokoly protinádorové kombinované chemoterapie; cyklofosfamid; imunoterapie; Aged, 80 and over; bendamustin hydrochlorid; Female; indukce remise; chronická lymfatická leukemie; lidé středního věku; staging nádorů; míra přežití; Middle Aged; Remission Induction